1188 Serial Quantitative C-Reactive Protein (QCRP) Concentrations to Determine Appropriateness of Antibiotics in Neonatal Sepsis: A Nested Case Control Study. (October 2012) - Patil, SS; Kumar, P; Ray, P; Verma, S
Abstract : Background and Aims: QCRP being acute phase reactant has predictable pattern of rise and fall following inflammation. Few studies have used QCRP for appropriateness of antibiotic therapy. To determine the difference in the magnitude of change in QCRP values from baseline to 48 h in subjects with culture positive neonatal sepsis receiving sensitive antibiotics (CPSA) versus those receiving resistant antibiotics (CPRA). Methods: Neonates < twenty-eight days with suspected sepsis and baseline QCRP >10 mg/L were enrolled. Serum samples at 24, 36 and 48 h after initiation of antibiotics were analyzed for QCRP (PETIA: Particle enhanced turbidimetric immunoassay). After collecting blood culture [BD BACTEC TM Peds Plus/F] report, CPSA and CPRA were cases and sterile cultures were controls. Mann-Whitney U test, linear regression, ROC curve and Youden's index were used to measure appropriateness of antibiotic therapy. Results: In one hundred forty-one sepsis episodes forty-five were CPSA, forty-four were CPRA and fifty two were culture sterile. The difference in QCRP between CPSA and CPRA was significant at all time points (p<0.001). The area under ROC curve was highest for ΔCRP0–48 [CRP (0 hr)-CRP (48 hr)] and ΔCRP24–48 [CRP (24 hr)-CRP (48 hr)] i.e 0.879 (CI: 0.80, 0.95) and 0.89 (CI: 0.81, 0.96) respectively. If ΔCRP0–48 was > 6.2 mg/L, the infant was likely to be getting sensitive antibiotics (sensitivity 86%, specificity 84%). Conclusion: A decrease in serum QCRP by 6.2 mg/L can be used as a useful indicator of the appropriateness of antibiotics in neonatal sepsis.